Prevalence of antibody against infectious bovine rhinotracheitis virus in sentinel cattle in West and East Nusa Tenggara - Agus Wiyono; Antonius Sarosa; Maria Goeng (Jurnal Ilmu Ternak dan Veteriner, 1995)
A total of 4,977 sera from a sentinel cattle in West and East Nusa Tenggara were tested for antibody against BHV-1, the causal agent of infectious bovine rhinotracheitis (IBR). These sera were collected between June 1990 and June 1993, and were tested by using serum neutralization test (SNT). Out of these sera, 3,713 were suitable for IBR SNT. A total of 349 sera (10.4%) reacted. IBR reactors were more prevalent in East Nusa Tenggara (NTT) than in West Nusa Tenggara (NTB) . Based on this survey, it is concluded that antibodies against IBR virus are present among cattle in East and West Nusa Tenggara .